Handbook of Research in Mobile Business 2006
DOI: 10.4018/978-1-59140-817-8.ch006
|View full text |Cite
|
Sign up to set email alerts
|

Mobility in Healthcare for Remote Intensive Care Unit Clinical Management

Abstract: This chapter reviews current research directions in healthcare mobility and assesses its impact on the provision of remote intensive care unit (ICU) clinical management. Intensive care units boast a range of state of the art medical monitoring devices to monitor a patient’s physiological parameters. They also have devices such as ventilators to offer mechanical life support. Computing and IT support within ICUs has focused on monitoring the patients and delivering corresponding alarms to care providers. Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…However, a recent survey ICU focused health informatics research [12], found that most researchers were not integrating patients or clinicians' mobility within their research.…”
Section: Service Of Critical Carementioning
confidence: 98%
“…However, a recent survey ICU focused health informatics research [12], found that most researchers were not integrating patients or clinicians' mobility within their research.…”
Section: Service Of Critical Carementioning
confidence: 98%
“…This research is part of the larger "e-Baby" research project (Foster & McGregor, 2006;McGregor, 2005;McGregor, Bryan, Curry, & Tracy, 2002;McGregor, Heath, & Wei, 2005;McGregor, Kneale, & Tracy, 2005, 2006. The broad aims of the e-Baby project are to develop:…”
Section: Related Workmentioning
confidence: 99%
“…The Availability Web Service forwards details of the receiving Neonatologist together with the details for the receiving Neonatologist's Physiological Web Service. Further details on Web services by NETS are contained in , 2006.…”
Section: Availability Web Servicementioning
confidence: 99%
See 2 more Smart Citations